Tourism Socialization: Training in Guiding Educational Songket Weaving Tours - Fernando Fasandra; Khairunnisa Khairunnisa; Naufal Hibatullah; Fadlul Rahman; Nitasri Murawaty Girsang; Septriani Septriani (Jurnal Masyarakat Religius dan Berwawasan, 2023)
Community service activities are one of the main responsibilities of lecturers as educators in the university environment. This community service aims to provide knowledge and improve the ability to guide educational tourism related to woven songket to enhance the promotion of SMEs through tourism. The community service activities are conducted at the SME "Rumah Songket Eka Halaban." The achieved results include an increase in participants' knowledge and skills in communicating with tourists, the hospitality of employees when tourists visit, and the application of the seven charms at Rumah Songket Eka Halaban. With these improved abilities, it is expected to boost the promotion of SMEs through tourism. The limitation of this community service activity lies in participants who are not yet accustomed to dealing with tourists with diverse backgrounds and characteristics. To be more effective in guiding educational tourism, considerable practice is needed. Similar community service activities can be conducted periodically by SMEs to familiarize themselves with dealing with tourists. With enhanced abilities, the training participants, including the owner of SME Rumah Songket Eka Halaban, hope that educational tourism activities related to woven songket can improve even further in the future.